Sensitivity of Boana pulchella (Anura: Hylidae) Tadpoles to Environmentally Relevant Concentrations of Chlorpyrifos: Effects at the Individual and Biochemical Levels. (22nd March 2020) - Barreto, Evelina; Salgado Costa, Carolina; Demetrio, Pablo; Lascano, Cecilia; Venturino, Andrés; Natale, Guillermo S.
Abstract : Experimental design performed to evaluate the toxicity of the insecticide chlorpyrifos on Boana pulchella larvae, at the individual and biochemical level. The multivariate approach allowed integrating all evaluated endpoints. Abstract: We report sublethal effects of environmentally relevant concentrations of chlorpyrifos at the individual (swimming alterations) and biochemical (esterase activities and antioxidant enzymes) levels in the Montevideo tree frog Boana pulchella larvae. The 50% lethal concentration at 96 h (LC50‐96h) for chlorpyrifos in stage‐29 B. pulchella tadpoles was 0.98 mg/L, which was close to the 65th percentile of published anuran species sensitivity. In B. pulchella, chlorpyrifos disrupted biochemical processes: tadpoles showed a significant inhibition of esterase activity and a significant induction of antioxidant enzymes, indicating a response to an environmental challenge causing oxidative stress. Using principal components analysis, we could associate chlorpyrifos reduction in esterase activity with swimming alterations at 0.5 mg/L of the toxicant. The biochemical biomarkers reported in the present study respond at levels 20 times lower than the LC50‐96h and were associated with a biologically important response—swimming behavior. The link of responses across different levels of biological organization was demonstrated. The species is suitable as a model for ecotoxicological studies at different levels, including the individual and biochemical levels, and may be considered a good reference organism in environmental control programs. Environ Toxicol Chem 2020;39:834–841. © 2020 SETAC